A Historical Review of the Molecular Phylogeny of the Philippine Nepenthes L. (Nepenthaceae) with Notes for Unsampled Taxa - Brillo, Samuel; Salamanes, Julius John; Austria, Eleanor (Journal of Interdisciplinary Perspectives, 2025)
Despite advances in molecular phylogenetics, the genus Nepenthes L., comprising about 180 species, presents a challenging phylogenetic puzzle due to morphological convergence. The Philippines (PH), a hotspot for pitcher plant diversity with 61 species, faces unclear evolutionary relationships due to insufficient taxon sampling. This historical review compiled the phylogenetic studies concerning Philippine Nepenthes from various molecular studies using nuclear or plastid markers. Here, we identified that the molecular phylogeny constructed from the angiosperms353 probe set used by Mullins et al. (2020) has given the most comprehensive results, with most samples from the Philippines and a total of 35 species compared to previously conducted phylogenies since 2000. It was revealed that these species form a large Philippine clade, split into three groups: Mindanao, Palawan, and Graciliflora, with other PH taxa belonging to the Insignes Clade. This study noted the possible clades of 26 unsampled PH taxa based on morphology and geography. Lastly, we created a distribution map of Philippine Nepenthes to support these placements. This study will help future research determine the phylogeny of Nepenthes in the Philippines, understand their evolutionary relationships with other paleotropical species, and assist policymakers in conserving these species from extinction.